Investigating student's cognitive engagement, motivation and cognitive retention in learning management system - Amin Husni, Nur Hanis (International Association of Online Engineering, 2022)
Online learning has grown significantly in recent years, due to the proliferation of online courses offered by universities. As a result, pedagogical guidance is critical for improving teaching quality in an online learning environment. In this study, Inquiry-Based Learning (IBL) activities were developed with the aim of increasing students' cognitive engagement, cognitive retention, and motivation to learn. This study also investigated the effects of the IBL pedagogical method on student performance. A pre-experimental study was conducted with 16 undergraduate students enrolled on a Multimedia Design and Human Computer Interaction course. Learning Analytics (LA) was used to retrieve research data from a Learning Management System (LMS) online discussion forum, and the data was then analyzed using content analysis and data mining analysis. According to the findings, students perceived a higher rate of low-level cognitive engagement but, interestingly, a high level of cognitive retention and motivation. Meanwhile, a significant relationship was observed between students' cognitive engagement, motivation and cognitive retention. © 2022, International Journal of Emerging Technologies in Learning.